An analysis of Individualism in Virtual Social Networks - Mohammad Rezaei; Mehdi Gholamzadeh (مطالعات رسانه‌های نوین, 2018)
The debate regarding the individuality or collectivity of the Iranian society is still alive among the Iranian scholars and sociologists. But, in these debate and also experimental researches on the individualism or collectivism of Iranian society one will notice that no attention has been paid to virtual social networks. However the participation in the virtual social networks has become an important part of Iranians` everyday life, and so it is necessary to examine collectivism and individualism with regard to these networks. In order to study this topic the following inquiry has been started by examining the networked individualism theory of Barry Wellman (2012) and after redefining of the concept, we have made a scale for measuring it. Therefore, one of the innovations in this study is creating a scale for this concept. The results showed that networked individualism exists at a moderate level. Also, the new findings suggest that familism, as a public culture of Iranian society in virtual networks also plays a significant role. Finally, it can be said that the networked individualism`s scale developed in this research, which has happened for the first time, can be a sufficient tool for the study of individualism in cyberspace that needs to be rectified and measured.